Comparative Analysis of Public Transportation Comfort in Addis Ababa: Objective and Subjective Performance Metrics - Shambel Assefa Esheti; Yonas Minalu Emagnu; Birhanu Demissie Haylemariam; Robeam Solomon Melaku (Modelling and Simulation in Engineering)
Passenger comfort significantly influences commuter satisfaction and mode preferences in urban transportation systems. To maintain competitiveness and attract more passengers, conducting continuous performance evaluations based on key performance indicators is commendable. Therefore, this study is aimed at conducting a mode-wide comfort performance evaluation and comparisons to identify the strengths and weaknesses of respective mass transport alternatives found in Addis Ababa, Ethiopia. The study employs a comprehensive approach by integrating both subjective surveys and objective measurements on key comfort determinants, including in-vehicle passenger loading, travel time, vibration, and sound, across five transport modes: minibus taxis, midi buses, PSETSE, Anbesa City Bus Service Enterprise (ACBE), and Sheger Mass Transport Enterprise (SMTE). Analysis of variance (ANOVA) reveals variations among transport modes, with minibus taxis emerging as the most comfortable, featuring a travel time of 1.7 min/km, 2.6 min/km during off-peak and peak times of the day, respectively, and an average of 1.13 passengers per seat in both periods of the day. In contrast, midi buses are identified as the least comfortable, characterized by elevated noise production (77.46 and 80 dB) and an average vibration rating of 3.9 and 4.2 at peak and off-peak periods of the day. Following midi buses, the ACBE exhibits the highest passenger loading and travel time (2.113 and 1.548 passengers per seat and takes 4.2 and 3.34 min) to cover 1 km during peak and off-peak periods, respectively. The holistic evaluation demonstrates an average correlation of 81.75%, indicating a strong alignment between peak-hour objective and subjective assessments. This could help commuters make relevant mode choice decisions and transport companies make market-oriented decisions in this competitive environment.